The potential for developing a sustainable fishing sector in Sukamara - Subianto, Pratiwi; Irawan, Irawan; Simbolon, Tiur Roida; Suherman, Suherman; Zakiah, Wiwin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This research explores the potential of a sustainable fisheries sector in Sukamara Regency, Central Kalimantan, which is rich in fisheries resources, both freshwater and marine. This study identified the potential for freshwater fish production of 10,000 tons annually and marine fish of 8,000 tons yearly, with superior species such as snakehead fish, baung, catfish, snapper, grouper, and tuna. Although the fishing sector has an essential role in the local economy, unsustainable fishing practices have led to overfishing, environmental degradation, infrastructure problems, and limited technological knowledge. This research emphasizes the importance of sustainable fisheries practices through ecosystem-based management, the use of environmentally friendly technology, and education and training programs to increase the capacity of fishermen. The economic impact shows an increase in the average income of fishermen by 25%, while the social impact includes an increase in the welfare of coastal communities by 20%. Environmental impacts include the restoration of mangrove and coral reef ecosystems with increased area and cover of live coral. The main challenges include overfishing, environmental degradation, lack of infrastructure, and limited technological knowledge. Proposed strategies to overcome these challenges include strengthening policies and regulations, improving infrastructure, education and training, multi-stakeholder collaboration, and research and development. By implementing this strategy, the potential of the sustainable fisheries sector in Sukamara can be optimized, providing significant economic, social, and environmental benefits and becoming a model for other regions in sustainable natural resource management.